The search for the holy grail: frugal innovation in healthcare from low-income or middle-income countries for reverse innovation to developed countries. Issue 4 (4th November 2017) - Bhatti, Yasser A; Prime, Matthew; Harris, Matthew; Wadge, Hester; McQueen, Julie; Patel, Hannah; Carter, Alexander W; Parston, Gregory; Darzi, Ara
Abstract : The healthcare sector stands to benefit most from frugal innovation, the idea that more can be done for less for many more people, globally. As a first step for health systems to leverage new approaches to offset escalating health expenditures and to improve health outcomes, the most relevant frugal innovations have to be found. The Institute of Global Health Innovation was commissioned by the US-based Commonwealth Fund to identify frugal innovations from around the world that could, if transferred to the USA, offer approaches for expanding access to care and dramatically lower costs. Our global scan was motivated by the need to extend the list of frugal innovations in healthcare beyond the impressive but oft-repeated examples such as GE's MAC 400, a US800 portable ECG machine, Narayana's US1500 cardiac surgery and Aravind's US30 cataract surgery. Our search involved (1) scanning innovation databases, (2) refining frameworks to identify frugal innovations and evaluate their reverse potential and (3) developing in-depth case studies. From 520 possible innovations, we shortlisted 16 frugal innovations that we considered as frugal and with potential for reverse diffusion into high-income country health systems. Our global search was narrowed down to three care delivery models for case analysis: The Brazilian Family Health Strategy around community health workers; Singapore-based GeriCare@North use of telemedicine and Brazil's Saude Crianca community involvement and citizenship programme. We share core features of the three frugal innovations and outline lessons for practitioners, scholars and policymakers seeking to lower healthcare costs while increasing access and quality.